Management of Atypical Symmetrical Ankylosis of Maxillary Deciduous First Molars with Permanent Successors: A Single Case Report - Gulduren, Kemal; İslam, Aylin (UI Scholars Hub, 2020)
Dentoalveolar ankylosis is the union between the tooth root and the dentoalveolar bone. Clinically, the affected tooth is unsuccessful to erupt, exhibits an infraocclusal position within the dentoalveolar arch, elicits a metallic sound on percussion, and has reduced or absent mobility. Objective: This single case report illustrates the management of idiopathically ankylosed maxillary deciduous first molars. Case report: The patient was a 6-year-old female with maxillary deciduous first molars in infraocclusal position due to idiopathic ankylosis. The ankylosed deciduous teeth were monitored regularly. After a 27-month follow-up, the infraocclusion became severe. No vertical deficiencies in other alveolar regions were detected. The ankylosed maxillary deciduous molars were extracted. After the extractions, vertical growth of the alveolar bone became normal and the maxillary first premolar successors erupted spontaneously. Conclusion: Conservative monitoring of ankylosed deciduous molars would be beneficial and preferred to prevent the impaction of permanent successors and manage the occlusion in a growing child. In case of severe infraocclusion, the deciduous molars may be extracted.